Government and NGOs Collaboration in Disaster Governance: The Indonesian Experience - Mubah, Ahmad Safril (Global and Policy Journal of International Relations, 2013)
ABSTRACTAs the main leader in disaster governance, governments are believed to have bigger role than the others. However, it is hard for governments to solve the disaster problems by themselves. Governments need to be supported by non-governmental organizations (NGOs) because NGOs have abilities which governments don’t have. Both of them must make mutual cooperation in disaster governance. But, the Indonesian experience shows that government and NGOs are, in some cases, involved in unnecessary conflict. Government views that the NGOs, mainly international NGOs, are just talking rather than acting and potential to destroy local knowledge. On the other hand, NGOs feel that the government could not respond the disaster quickly and want to restrict their freedom. Therefore, to give the best service for disaster victims, government and NGOs should make norms for collaboration and coordination among them, hold regular training of disaster risk reduction for government officials, and improve capacity building support needed by NGOs.Key Words: government, NGOs, disaster governance, disaster risk reduction.DOI:https://doi.org/10.33005/jgp.v1i01.2005